ACETIC ACID REMEDIATION OF ANTHROPOGENIC CONTAMINATION OF WATER AT THE GBNERR IN MISSISSIPPI - Farah, Ibrahim O; Lyons, Willis O; Arslan, Zikri; Tucci, Michelle; Tchounwou, Paul B (Biomedical sciences instrumentation, 2018)
Grand Bay National Estuarine Research Reserve (GBNERR) is an important ecosystem in the Mississippi Gulf Coast. The GBNERR may be a potential source for contamination with anthropogenic bacterial pathogens that may play a significant role in the causation of waterborne human diseases. The objective of this study was to evaluate the interaction of physicochemical and microbiological water quality parameters at the GBNERR to determine quantitative levels and establish the potential for remediation of post-contamination of water and seafood by human fecal pollution from anthropogenic sources at the reserve. Water samples were collected aseptically from Bayous Heron, Cumbest, Point Aux Chenes Bay and Bangs Lake (Pine-O-Pine). Physicochemical parameters were determined using standard protocols. Eight bacterial species including Campylobacter were concentrated from water samples by membrane filtration. Water samples were tested for the presence of traditional indicator microorganisms including: heterotrophic (HPC), total coliforms (TC), fecal coliforms (FC), and enterococcus (ENT) in CFU/ml concentrations. Mean values of temperature, specific conductivity, dissolved oxygen, and pH were within acceptable levels in comparison to MDEQ, USEPA, and the USGS standards during the time of investigation. However, the values of turbidity in Grand Bay water exceeded USEPA recommended levels in several occasions during the investigation. Data from this study indicates significant variability (p < 0.0001) in mean bacteria concentrations between sites. The data also indicates significant impact of acetic acid treatment in the remediation of post contamination and survival of pathogens from the GBNERR Bayous Heron, Cumbest, and Pine-O-Pine when compared with control findings. The interaction of physicochemical and microbiological parameters of water through external chemical manipulation by acetic acid may provide utility in the remediation of post-contamination with anthropogenic pathogens such as , Enterococci, Campylobacter, Vibrio, Giardia, and Cryptosporidium. Presence of high numbers of indicator bacteria suggests public health concerns for oyster and shellfish consumers as well as other water contact activities. Hence, control strategies should be developed and implemented to prevent or remediate any future contamination of the GBNERR waters citing the economic impact of such contamination on shellfish fishing activities on the reserve.